Evaluation of different sterilization and disinfection methods on commercially made preformed crowns - Yilmaz Y; Guler C (Wolters Kluwer Medknow Publications, 2008)
The aim of this study was to evaluate the changes caused by different sterilization or disinfection methods on the vestibular surface of four commercially made preformed crowns using stereomicroscopy and scanning electron microscopy (SEM). Preformed crowns (NuSmile Primary Anterior Crown (NSC), Kinder Krowns (KK), Pedo Pearls (PP) and polycarbonate crowns (PC)) were sterilized and/or disinfected by one of the following techniques: no sterilization or disinfection (G1 control group); steam autoclaving at 134 °C (30 psi) for 4 min (G2); steam autoclaving at 134 °C (30 psi) for 12 min (G3); steam autoclaving at 121 °C (15 psi) for 30 min (G4); and ultrasonication in a bath containing 4% Lysetol ® AF for 5 min at room temperature (chemical disinfection) (G5). Scanning electron micrographs of the crowns were taken before and after their sterilization or disinfection. The changes on the vestibular surface were then scored for the presence or absence of crazing, contour alteration, fracturing, and vestibular surface changes. The data were analyzed statistically using the chi-square test. No changes were observed before and after sterilization or disinfection in the stereomicroscopic evaluation of the vestibular surface of the crowns. However, all methods in which steam autoclaving was used to sterilize the crowns caused significant (P < 0.05) crazing and contour alterations of the vestibular surface of the crowns when they were examined by SEM. Chemical disinfection using an aldehyde-free disinfectant is the preferred method of disinfection for crowns that have been used previously in other dental patients.